Neurologic and other systemic manifestations in FMF: Published and own experience - Feld, O.; Yahalom, G.; Livneh, A. (Best practice & research. Clinical rheumatology, 2012)
Familial Mediterranean fever (FMF) is an autosomal recessive autoinflammatory disease, presenting with recurrent episodes of fever and polyserositis. Neurologic involvement in FMF is rare and usually considered fortuitous. The aim of this article is to review the spectrum of possible neurologic manifestations, which can be encountered in FMF patients, and to establish their relation to FMF. We reviewed the literature based on Pubmed search to find neurologic manifestations, which were reported in FMF patients. To that we added our own experience on the subject, abstracted from our computerised FMF registry of 12000 FMF patients of the National FMF Center and the computerised database of Sheba Medical Center. A wide range of neurologic manifestations involving FMF patients was noted. A large part of these manifestations could be directly related to FMF, its complications, associated diseases and treatment adverse effects. The remaining were incidental, or of uncertain association to FMF. A physician, taking care of an FMF patient, can face various neurologic manifestations and should be aware of their origin. The current chapter provides an insight to this association of FMF.